Proceso de descentralización y calidad de los servicios públicos locales en el distrito de Requena 2024 - Gaviria Rios, James William (2025)
The present final report aimed to determine the relationship between the decentralization process and the quality of local public services in the Requena District 2024. Developing under a basic method, descriptive correlational level with a non-experimental design, where 378 users were taken as a study sample, to whom a survey was used to collect information. The results showed that the decentralization process is regular (26%), this is because the inherent functions of the local government are sometimes developed effectively, as well as the municipality sometimes innovates in the provision of public services, and the collection of rents and income of the district is sometimes efficient. Regarding the quality of local public services, 25% indicated that it is average, since the equipment and tools used in the services are sometimes adequate, however, the electric service almost always works without interruptions, but the staff sometimes has the capacity to attend emergencies efficiently, and sometimes feels safe when using the district's public services, finally, the staff is sometimes kind and respectful. A positive and significant relationship was found between decentralization and the quality of local public services, with a Rho coefficient of 0.775 and statistical significance (p=0.000). In addition, a moderate positive relationship was observed between the political dimension and the quality of services (r=0.672; p=0.000). The relationship between the administrative dimension and the quality of services was positive and strong (r=0.718; p=0.000), while the economic dimension showed a moderate positive relationship with the quality of local public services (r=0.667; p=0.000).